The behavioralist goes to school: Leveraging behavioral economics to improve educational performance - Steven D. Levitt; John A. List; Susanne Neckermann; Sally Sado (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Decades of research on behavioral economics have established the importance of factors that are typically absent from the standard economic framework: reference dependent preferences, hyperbolic preferences, and the value placed on non-financial rewards. To date, these insights have had little impact on the way the educational system operates. Through a series of field experiments involving thousands of primary and secondary school students, we demonstrate the power of behavioral economics to influence educational performance. Several insights emerge. First, we find that incentives framed as losses have more robust effects than comparable incentives framed as gains. Second, we find that non-financial incentives are considerably more cost-effective than financial incentives for younger students, but were not effective with older students. Finally, and perhaps most importantly, consistent with hyperbolic discounting, all motivating power of the incentives vanishes when rewards are handed out with a delay. Since the rewards to educational investment virtually always come with a delay, our results suggest that the current set of incentives may lead to underinvestment. For policymakers, our findings imply that in the absence of immediate incentives, many students put forth low effort on standardized tests, which may create biases in measures of student ability, teacher value added, school quality, and achievement gaps.
urn:nbn:de:bsz:180-madoc-323358
Keywords: 330; educational economics; behavioral economics; field experiment; Schüler; Bildungsverhalten; Verhaltensökonomik; Motivation; Ökonomischer Anreiz; Bildungsökonomik; Feldforschung; Schätzung; USA